1997
DOI: 10.1016/s0092-8674(00)80332-3
|View full text |Cite
|
Sign up to set email alerts
|

Costal2, a Novel Kinesin-Related Protein in the Hedgehog Signaling Pathway

Abstract: The Hedgehog (HH) signaling proteins control cell fates and patterning during animal development. In Drosophila, HH protein induces the transcription of target genes encoding secondary signals such as DPP and WG proteins by opposing a repressor system. The repressors include Costal2, protein kinase A, and the HH receptor Patched. Like HH, the kinase Fused and the transcription factor Cubitus interruptus (CI) act positively upon targets. Here we show that costal2 encodes a kinesin-related protein that accumulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
246
1
2

Year Published

1998
1998
2007
2007

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 315 publications
(261 citation statements)
references
References 63 publications
12
246
1
2
Order By: Relevance
“…However, the effects of cos2 loss of function can be examined in adult structures through mosaic analysis. Clones of cells in far anterior regions of the A compartment of the wing imaginal disc that lack cos2 trigger anterior overgrowth phenotypes, and activation of low level Hh target genes, suggesting a negative regulatory role [23,66,67,71]. However, cos2 clones near the A/P compartment boundary do not express high level Hh-target genes, suggesting a role for Cos2 in activation of Ci [48,66,71].…”
Section: Costal2mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the effects of cos2 loss of function can be examined in adult structures through mosaic analysis. Clones of cells in far anterior regions of the A compartment of the wing imaginal disc that lack cos2 trigger anterior overgrowth phenotypes, and activation of low level Hh target genes, suggesting a negative regulatory role [23,66,67,71]. However, cos2 clones near the A/P compartment boundary do not express high level Hh-target genes, suggesting a role for Cos2 in activation of Ci [48,66,71].…”
Section: Costal2mentioning
confidence: 99%
“…Cos2 shares homology with the family of Kinesin-related protein (KRP) molecular motors [23]. KRPs bind vesicular membranes and microtubules (MT) in a highly regulated manner, and can facilitate movement along MTs through ATP hydrolysis (reviewed in [77]).…”
Section: Costal2mentioning
confidence: 99%
“…More surprisingly, interactions may also take place that involve kinesins as the MLK2 kinase (5) or the tumor suppressor APC were shown to interact with the kinesin-like KIF3 (55). Cubitus interruptus is bound to the kinesin-related protein Costal 2 in the Hedgehog signaling pathway (56,57), and JIP scaffolding proteins for the JNK signaling pathway were found to bind conventional kinesin (58). Regarding the case of STAT5B, dynein-mediated trafficking along MTs is consistent with the fact that STAT5 and the GR may translocate together into the nucleus (34) and that the GR associates with the dynein intermediate chain (39).…”
Section: Figmentioning
confidence: 99%
“…Epistatic relationships suggested that, in addition to hedgehog, other members of this pathway included patched, the serpentine membrane protein smoothened (smo; Alcedo et al, 1996;van den Heuvel and Ingham, 1996), the kinesinlike protein costal-2 (cos-2; Sisson et al, 1997), the serine/threonine kinase fused (fu; Preat et al, 1990), the novel protein suppressor of fused (Monnier et al, 1998), and the zinc ®nger transcription factor cubitus interruptus (ci; Orenic et al, 1990). Initial studies of this signalling pathway focused on the hedgehog molecule whose expression de®nes the development of many embryonic and adult structures in both the¯y and vertebrates.…”
Section: Hedgehog Signalling Pathwaymentioning
confidence: 99%